Strengthening participatory governance for Generation Z: A case study of Karang Taruna Meruya Selatan, West Jakarta - Devid Putra Arda (Jurnal Bisnis Mahasiswa, 2026)
Purpose – This study examines the participatory governance practices of Generation Z in Karang Taruna Meruya Selatan, West Jakarta, focusing on their role in improving organizational transparency, accountability, inclusiveness, and responsiveness. Design/methodology/approach – A descriptive and interpretive qualitative approach was used, with data collected through in-depth interviews, focus group discussions, participatory observation, and document analysis. Thematic analysis supported by triangulation of sources and methods was used to ensure data credibility. Findings – Findings show that Generation Z actively utilizes digital platforms, such as WhatsApp, Instagram, and Google Forms, to express ideas, coordinate activities, and collaborate in program design. However, their participation is still limited by hierarchical structures, limited decision-making authority, and weak follow-up mechanisms. Digital literacy significantly shapes the effectiveness of communication and influences the depth of participation. Research limitations – This study is limited to one youth community organization, namely Karang Taruna Meruya Selatan Jakarta Barat; therefore, these findings may not be widely applicable. Implications – This research has implications for youth studies and participatory governance by highlighting patterns of digital participation and proposing youth empowerment practices relevant to the local community context. Originality – The uniqueness of this research lies in the integration of generational theory with Arnstein's Ladder of Participation, offering a unique analytical framework for understanding youth involvement in community organizations in Indonesia's digital era.